Local food as resistance: Integrating women’s experiences in the Hungarian food sovereignty movement - Bródy, Luca Sára; Farkas, Judit; Gál, Izóra; Milánkovics, Kinga; Nagy, Erika; Sági, Mirjam (Intersections. East European Journal of Society and Politics, 2024)
The weak civil society thesis in Central and Eastern Europe (CEE) has been central to scholarly debates interpreting civil society from a Western lens. Touching upon the issue of food sovereignty, we contest this conceptualisation by revealing the wider networks and strength of food-related local practices in Hungary after the 1990s. In doing so, we rely on a qualitative study conducted between 2020-2021, based on 25 semi-structured ‘oral herstory’ interviews with women who have been actively dealing with food sovereignty issues. With the above study, we had three main objectives. First, to counter the widespread (mis)perception of local food production as a mere necessity in CEE. Second, we highlight the importance of rural local food production, to counter the understanding of home gardening as a practice without resistance. Thirdly, we wish to voice the experiences of women in the movement in their larger structural and historical settings. Our findings concentrate on two key areas: the movement’s experience with recurrent crises and political-economic conditions from the 1990s onwards, and the subjective assessment of shifting hierarchical dynamics within the movement milieu. The paper’s main goal is to illuminate women’s experiences and positionality within the global food system from a Hungarian viewpoint.